2014
DOI: 10.1017/s0305000914000592
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linguistic interaction in trilingual phonological development: the role of the input in the acquisition of the voicing contrast

Abstract: This paper examines the production of word-initial stops by two simultaneous trilingual sisters, aged 6;8 and 8;1, who receive regular input in Italian and English from multiple

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 40 publications
4
25
0
1
Order By: Relevance
“…The results of the present study specifically show that there are factors beyond CLI that can contribute to these differences in the speech of bilingual and monolingual children. The present study furthermore supports previous case studies describing striking similarities between the input and bilingual children's speech production with statistical evidence (Deuchar & Clark, 1996;Khattab, 2003;Klinger, 1962;Mayr & Montanari, 2015). In sum, when phonetic aspects of the speech of bilingual children differ from monolingual children, this can in part be attributed to differences in their input.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the present study specifically show that there are factors beyond CLI that can contribute to these differences in the speech of bilingual and monolingual children. The present study furthermore supports previous case studies describing striking similarities between the input and bilingual children's speech production with statistical evidence (Deuchar & Clark, 1996;Khattab, 2003;Klinger, 1962;Mayr & Montanari, 2015). In sum, when phonetic aspects of the speech of bilingual children differ from monolingual children, this can in part be attributed to differences in their input.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the outcome of this study, we hypothesize that a positive association exists between maternal VOT and the VOT production of both bilingual and monolingual children. This hypothesis is based on previous research, which reported maternal input effects in monolingual children's lexical growth (Hoff, 2003;Hurtado et al, 2008;Rowe, 2008Rowe, , 2012Rowe et al, 2012) and observations of similarities between phonetic aspects of the input and the speech of monolingual children (Foulkes et al, 1999) and bilingual children (Deuchar & Clark, 1996;Khattab, 2003;Klinger, 1962;Mayr & Montanari, 2015). Given that the bilingual children's regular exposure to German is restricted to their mothers, we hypothesize that the association is stronger in German than in Dutch.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Many studies have examined stop consonants acoustically (e.g., Bortolini et al, 1995;Kirkham, 2011;Mayr & Montanari, 2015;Sundara, 2005). While temporal measures, such as voice onset time (VOT), allow for direct comparisons between child and adult participants, this is not the case for spectral measures that aim to assess differences in place of articulation as they vary with vocal tract size.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contexts of reduced input, as in the present case, nonnative patterns may be influential for the next generation of speakers. Mayr & Montanari (2015), for instance, showed that multilingual children who only receive input in one of their languages from a single speaker are highly responsive to their patterns and home in on speaker-specific phonetic information. Hence, since the GEN 3 CHILDREN have restricted exposure to Sylheti, their mothers' non-native productions may be partly responsible for their own non-native realisations in the heritage language.…”
Section: Acquisition Patterns: Childrenmentioning
confidence: 99%